Military Budget and Economic Growth: Case of Middle East, North Africa and South Asia Countries - Ratni Heliati; Intan Putri Wandiva (TRIKONOMIKA, 2017)
Conflict became one of the biggest problems in the Middle East region. This situation will deteriorated the country and will impact on economic perfomance, so defense budget is important to resolve these problems. This study aims to determine the effect of military budget on economic perfomance in 22 countries of the Middle East, North Africa and South Asia 2000-2014 period. This study uses 5 variables namely GDP per capita, military budget, gross capital formation, human capital and final consumption expenditure. This study uses panel data analysis with fixed effect model. The results of model estimation suggest that military budget has a significant negative effect on economic perfomance, while gross capital formation, final consumption expenditure have significant positive effect on economic perfomance. Meanwhile, human capital does not have significant effect on economic perfomance in 22 countries.